Involvement of Glutathione Depletion in Selective Cytotoxicity of Oridonin to p53-Mutant Esophageal Squamous Carcinoma Cells - Li, Yinchao; Li, Nana; Shi, Jianxiang; Ahmed, Tanzeel; Liu, Hongmin; Guo, Jiancheng; Tang, Wenxue; Guo, Yongjun; Zhang, Qi (Frontiers in Oncology, 2020)
Oridonin, a diterpenoid compound isolated from traditional Chinese medicine Rabdosia rubescens, has shown antitumor effects to esophageal cancer. However, its molecular mechanism is not fully understood, which limits its clinical application. In the present study, we used RNA-seq analysis to check the transcriptome changes after oridonin treatment and we found genes controlling GSH-ROS system were up-regulated, namely SLC7A11, TXNRD1, TRIM16, SRXN1, GCLM and GCLC. Further, our data suggest that oridonin significantly increased production of ROS in EC109 and TE1 cells, which can be inhibited by NAC (P <0.01). Interestingly, oridonin can dramatically reduce intracellular GSH levels in TE1 cells in a concentration and time-dependent manner (P <0.01), in addition, cell death caused by oridonin was strongly inhibited by GSH (1 mM, P <0.01), while GSSG (1 mM) had little effect. At the same time, we also found that oridonin showed selective cytotoxicity to esophageal squamous carcinoma cell with p53 mutation since mut-p53 cells had lower SLC7A11 expression, a component of the cystine/glutamate antiporter. We also found that γ-glutamyl cysteine synthetase inhibitor（BSO）synergizes with oridonin to strongly inhibit EC109 cells at a low dose. These results suggested that the antitumor effects of oridonin are based on its –SH reactive and glutathione depletion. Esophageal squamous carcinoma cells with p53-mutation showed hypersensitivity to oridonin because of SLC7A11 expression inhibited by p53 mutation.